Cost-utility analysis of trabecular micro-bypass stents (TBS) in patients with mild-to-moderate open-angle Glaucoma in Italy - Antonio Maria Fea; Francesco Cattel; Stefano Gandolfi; Giorgio Buseghin; Gianluca Furneri; Ciro Costagliola (BMC, 2021)
Abstract Background Glaucoma is a disease characterized by progressive damage of the optic nerve. Several therapeutic options are available to lower intraocular pressure (IOP). In primary open-angle glaucoma (POAG) patients with inadequate IOP control (or controlled with multiple medical therapies or for whom medical therapy is contraindicated), the implantation of micro-invasive glaucoma surgery devices (MIGS) and concomitant cataract surgery has proved to be more effective in reducing intraocular pressure (IOP), as compared to cataract surgery alone. The objective of this study was to assess the cost-effectiveness of iStent inject® device with concurrent cataract surgery vs. cataract surgery alone, in patients with mild-to-moderate POAG, adopting the Italian National Health Service (NHS) perspective. Methods Simulation of outcomes and costs was undertaken using a Markov model with 4 health states and one-month cycles, that is used to simulate the prognosis of these patients. Efficacy data were obtained from the randomized clinical trial (RCT). A lifetime horizon was adopted in the analysis. A discount rate of 3.5% was applied to both costs and effects. The Italian National Healthcare Service (NHS) perspective was considered, therefore only healthcare direct costs (acquisition of main interventions and subsequent procedures; medications; monitoring and follow-up; adverse events). Model robustness was tested through sensitivity analyses. Results Results of the base-case analysis showed that the total lifetime costs were higher in the iStent inject® + concurrent cataract surgery, compared with the cataract surgery alone group (€8368.51 vs. €7134.71 respectively). iStent inject® + concurrent cataract surgery was cost-effective vs. cataract surgery alone, with an incremental cost-effectiveness ratio of €13,037.01 per quality-adjusted life year (QALY) gained. Both one-way deterministic and probabilistic sensitivity analyses confirmed robustness of base-case results. The cost-effectiveness accessibility curve (CEAC) showed that iStent inject® + cataract surgery would have a 98% probability of being cost-effective, compared to cataract surgery alone, when the willingness to pay (WTP) is equal to €50,000 per QALY gained. Conclusions The results of the cost-utility analysis confirm that iStent inject® + cataract surgery is a cost-effective option for the treatment of patients affected by mild-to-moderate POAG, compared with cataract surgery alone, when evaluated from the Italian NHS perspective.